Archaeological geophysics in Israel: past, present and future - L. V. Eppelbaum (Advances in Geosciences, 2010)
In Israel occur a giant number of archaeological objects of various age, origin and size. Different kinds of noise complicate geophysical methods employment at archaeological sites. Geodynamical active, multi-layered, and geologically variable surrounding media in many cases damages ancient objects and disturbs their physical properties. This calls to application of different geophysical methods armed by the modern interpretation technology. The main attention is focused on the geophysical methods most frequently applying in Israeli archaeological sites: GPR and high-precise magnetic survey. Other methods (paleomagnetic, resistivity, near-surface seismics, piezoelectric, etc.) are briefly described and reviewed. The number of employed geophysical methodologies is constantly increasing, and now Israeli territory may be considered as a peculiar polygon for various geophysical methods testing. Several examples illustrate effective application of geophysical methods over some typical archaeological remains. The geophysical investigations at archaeological sites in Israel could be tentatively divided on three stages: (1) past (1990), (2) present (1990–2009), and (3) future (2010). The past stage with several archaeoseismic reviews and very limited application of geophysical methods was replaced by the present stage with the violent employment of numerous geophysical techniques. It is supposed that the future stage will be characterized by extensive development of multidiscipline physical-archaeological databases, employment of all possible indicators for 4-D monitoring and ancient sites reconstruction, as well as application of combined geophysical multilevel surveys using remote operated vehicles at low altitudes.